2005
DOI: 10.1038/ng1528
|View full text |Cite|
|
Sign up to set email alerts
|

Frequent somatic mutations of the transcription factor ATBF1 in human prostate cancer

Abstract: Cancer often results from the accumulation of multiple genetic alterations. Although most malignancies are sporadic, only a small number of genes have been shown to undergo frequent mutations in sporadic cancers. The long arm of chromosome 16 is frequently deleted in human cancers, but the target gene for this deletion has not been identified. Here we report that ATBF1, which encodes a transcription factor that negatively regulates AFP and MYB but transactivates CDKN1A, is a good candidate for the 16q22 tumor-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
181
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(193 citation statements)
references
References 24 publications
11
181
0
Order By: Relevance
“…38 Moreover, ATBF1 was recently identified as a tumor suppressor gene. 19 These observations suggest that ATBF1 localization in the nucleus suppresses MUC5AC in gastric cancer and results in better prognosis. MUC5AC expression might be an indicator of the characteristics of different gastric cancers by associating with the function of ATBF1.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…38 Moreover, ATBF1 was recently identified as a tumor suppressor gene. 19 These observations suggest that ATBF1 localization in the nucleus suppresses MUC5AC in gastric cancer and results in better prognosis. MUC5AC expression might be an indicator of the characteristics of different gastric cancers by associating with the function of ATBF1.…”
Section: Discussionmentioning
confidence: 85%
“…17,18 These observations are consistent with the recent identification of ATBF1 as a tumor suppressor. 19 Thus, not only the expression levels of ATBF1, but also its subcellular localization, appear to be linked to cell differentiation and induction of cell cycle arrest. 20 The present study of mucin expression in gastric cancer and the functions of ATBF1 [21][22][23] has revealed that the expression of ATBF1 in the nucleus suppresses MUC5AC expression in gastric cancer.…”
mentioning
confidence: 99%
“…Using a microarray analysis and quantitative PCR validation (39) of TRAMP-AR pe-T877A/Y mice, we observed the expected alterations in tumor genes such as TERT and Cdk2 (40,41) and the tumor suppressor genes NKX3.1, ATBF1, and p21 (42,43) (Fig. S3).…”
Section: Discussionmentioning
confidence: 92%
“…All tumor and matched normal cells were collected from H&E stained sections of formalin-fixed, paraffin-embedded tissues by manual microdissection, as described in our previous study (Dong et al, 2000). All prostatic epithelial cell lines and xenografts were described in our previous studies (Chen et al, 2003a, b;Sun et al, 2005).…”
Section: Methodsmentioning
confidence: 99%